CLIMATE CHANGE AS A POLITICAL ISSUE: INTERNATIONAL COOPERATION AND THE ROLE OF GLOBAL GOVERNANCE - Perveez Ahmad Khan (CV. Radja Publika, 2025)
Climate change has emerged not only as an environmental and scientific concern but as a profoundly political issue, shaping and being shaped by international relations, economic development, and power dynamics. This paper examines the political dimensions of climate change, emphasizing the role of international cooperation and global governance in addressing the crisis. It analyzes key multilateral frameworks such as the UNFCCC and the Paris Agreement, as well as the contributions of institutions like the IPCC. Despite growing consensus and increased participation, effective global action is undermined by geopolitical tensions, inequality, and weak enforcement mechanisms. The study argues that while progress has been made, significant reforms in global governance focused on equity, transparency, and accountability are essential for achieving meaningful and lasting climate outcomes.